Progress in Assays of HMGB1 Levels in Human Plasma-The Potential Prognostic Value in COVID-19 - Štros, Michal; Polanská, Eva Volfová; Hlaváčová, Tereza; Skládal, Petr (Biomolecules, 2022)
Extracellular HMGB1 protein is known to induce inflammatory responses leading to an inflammatory storm. The outbreak of the Severe Acute Respiratory Syndrome COVID-19 due to the SARS-CoV-2 virus has resulted in a huge health concern worldwide. Recent data revealed that plasma/serum HMGB1 levels of patients suffering from inflammation-mediated disorders-such as COVID-19, cancer, and autoimmune disorders-correlate positively with disease severity and vice versa. A late release of HMGB1 in sepsis suggests the existence of a wide therapeutic window for treating sepsis. Rapid and accurate methods for the detection of HMGB1 levels in plasma/serum are, therefore, of great importance for monitoring the occurrence, treatment success, and survival prediction of patients with inflammation-mediated diseases. In this review, we briefly explain the role of HMGB1 in the cell, and particularly the involvement of extracellular HMGB1 (released from the cells) in inflammation-mediated diseases, with an emphasis on COVID-19. The current assays to measure HMGB1 levels in human plasma-Western blotting, ELISA, EMSA, and a new approach based on electrochemical immunosensors, including some of our preliminary results-are presented and thoroughly discussed.
Keywords: imunoanalýza; protein HMGB1; Sepsis; biosenzitivní techniky; EMSA; Prognosis; Immunoassay; SARS-CoV-2; HMGB1 Protein; COVID-19; Biosensing Techniques; HMGB1; immunosensor; prognóza; ELISA; Humans; plasma/serum; sepse; lidé